Dietary bamboo charcoal powder ameliorates high-fat diet-induced hyperlipidemia by enhancing fecal lipid excretions in Sprague–Dawley rats - Jia, Zhenchao; Zhou, Yongru; Chen, Xuxi; Zhang, Lishi; Li, Yan; Chen, Jinyao (Frontiers in Nutrition, 2024)
Introduction: Bamboo charcoal powder (BCP) is increasingly used as a food colorant. This study aimed to evaluate the effects of BCP consumption on improving high-fat diet-induced hyperlipidemia.Methods: Fifty male SD rats were randomly assigned into five groups: the control group fed a lowfat diet (LFD); the model control group fed a high-fat diet (HFD); the low-BCP dose group fed a HFD and given 2.81 g of BCP/kg of body weight (BCP-L) by gavage; the medium-BCP dose group fed a HFD and given 5.62 g of BCP /kg of body weight (BCP-M) by gavage; the high-BCP dose group fed a HFD and given 11.24 g of BCP/kg of body weight (BCP-H) by gavage, with 10 rats in each group. Results: After 90 days, the consumption of BCP caused a decrease in body weight, plasma lipid (triglyceride, cholesterol, and LDL), liver triglyceride, and cholesterol levels, and liver histopathological scores. BCP caused a significant increase in Superoxide Dismutase (SOD) activity and Total antioxidant capacity (T-AOC) in liver tissues. BCP also led to an increase in 72-h fecal dry weight and crude fat in a rat metabolic cage. Analysis of fecal samples with liquid chromatography time-of-flight mass spectrometry (LC-Q-TOF-MS) showed that the biomarkers associated with BCP consumption were mainly related to fatty and amino acid metabolism. Notably, BCP treatment significantly promoted linoleic acid metabolism. Discussion: These results suggest that BCP may have a preventive effect against diet-induced hyperlipidemia through the promotion of fecal fat excretion. BCP may potentially be used as an alternative functional food component for people with diet-induced hyperlipidemia.